Multifunction broom - Khairil Anwar, Abu Bakar (2010)
There are many brooms in the market. Broom or sweeper is more synonymous with collecting and cleaning duties. Today, broom was readily adopted into the sweeper with a variety of shapes and patterns. It is the origin of the stick has been modernized with the use of plastic as the main ingredient. However, there is the design and creation of a multifunction wiper market. By creating a multifunction broom is expected not only to attract the attention of consumers because of patterns and designs are more effective cured but can help users perform work such as sweeping, cleaning floors and mirrors using only one tool only, and indirect cost savings in consumer spending. The results indicate the project objective to produce a variety of functions and can be used for a variety of situations is achieved.